Novel compound heterozygous CDH23 variants in a patient with Usher syndrome type I - Okano, Satomi (Hum Genome Var, 2019)
Usher syndrome type I (USH1) is characterized by congenital, bilateral, profound sensorineural hearing loss, vestibular areflexia, and adolescent-onset retinitis pigmentosa. Here, we report a 12-year-old female patient with typical USH1. Targeted panel sequencing revealed compound heterozygous variants of the Cadherin 23 (CDH23) gene, which confirmed the USH1 diagnosis. A novel NM_022124.5:c.130G>A/p.(Glu44Lys) was identified, expanding the mutation spectrum of CDH23.